Development of an in vitro cell system from zebrafish suitable to study bone cell differentiation and extracellular matrix mineralization - Vijayakumar, Parameswaran (2018)
Mechanisms of bone formation and skeletal development have been successfully investigated in zebrafish using a variety of in vivo approaches, but in vitro studies have been hindered due to a lack of homologous cell lines capable of producing an extracellular matrix (ECM) suitable for mineral deposition. Here we describe the development and characterization of a new cell line termed ZFB1, derived from zebrafish calcified tissues. ZFB1 cells have an epithelium-like phenotype, grow at 28 degrees C in a regular L-15 medium supplemented with 15% of fetal bovine serum, and are maintained and manipulated using standard methods (e.g., trypsinization, cryopreservation, and transfection). They can therefore be propagated and maintained easily in most cell culture facilities. ZFB1 cells show aneuploidy with 2n=78 chromosomes, indicative of cell transformation. Furthermore, because DNA can be efficiently delivered into their intracellular space by nucleofection, ZFB1 cells are suitable for gene targeting approaches and for assessing gene promoter activity. ZFB1 cells can also differentiate toward osteoblast or chondroblast lineages, as demonstrated by expression of osteoblast- and chondrocyte-specific markers, they exhibit an alkaline phosphatase activity, a marker of bone formation in vivo, and they can mineralize their ECM. Therefore, they represent a valuable zebrafish-derived in vitro system for investigating bone cell differentiation and extracellular matrix mineralization.